N-[Ethyl(2-hydroxyethyl)carbamothioyl]-2-methylbenzamide - Yamin, Bohari M. (International Union of Crystallography, 2014)
The title compound, C(13)H(18)N(2)O(2)S, adopts a cis conformation between the methylbenzoyl and thiono groups across their thiourea C—N bond. However, the methylbenzoyl group and N(2)CS thiourea moiety are twisted by 15.03 (3)°. In the molecule there is an N—H⋯O hydrogen bond. In the crystal, molecules are linked by O—H⋯O interactions, generating chains extending along the c-axis direction.